2015
DOI: 10.1016/j.jtumed.2014.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of knowledge, generic skills and attitudes through problem-based learning: Student perspectives in a hybrid curriculum

Abstract: Objective: To investigate students' perceptions of problem-based learning in the acquisition of relevant knowledge, generic skills and attitudes in a setting where this is a vital component of the medical undergraduate hybrid curriculum.Methods: 464 undergraduate medical students in four consecutive batches (two in the first year and two in the second year of the medicine programme) at Melaka Manipal Medical College were enrolled in this crosssectional study. A pre-validated questionnaire with 15 items classif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 6 publications
1
20
0
7
Order By: Relevance
“…al, 2008) and language skills (Mardziah H. Abdullah & Tan, 2008;Norzaini Azman & Shin, 2012;Othman & Ismail Ahmad Shah, 2013). It also helps students in the acquisition of subject content/knowledge (Hande, Mohammed & Komattil, 2014), life-long learning (Hosseini & Assareh, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…al, 2008) and language skills (Mardziah H. Abdullah & Tan, 2008;Norzaini Azman & Shin, 2012;Othman & Ismail Ahmad Shah, 2013). It also helps students in the acquisition of subject content/knowledge (Hande, Mohammed & Komattil, 2014), life-long learning (Hosseini & Assareh, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The current study provides a preliminary insight into the perception of students from a Romanian university about developing generic skills and into their readiness to assume the role of main actors in the learning process. We consider this information valuable as it represents a starting point for the elaboration of any curricula improvement or education strategy (Bedwell et al, 2014;Chan, 2010;Faherty, 2015;Hande et al, 2015;Massaro et al, 2016). Investigating the students' perceptions and their opinions we can better understand their needs and in this way, we can provide more satisfaction by offering more appropriate education services.…”
Section: Discussionmentioning
confidence: 99%
“…This type of skills may be learnt from other individuals while they are using them in practice (Curtis, 2004). Generic skills are especially important for students' future career because they are considered the most useful in terms of increasing their chances of getting employed for the appropriate job, in the field of their education, motivation and personality traits (Hande, Mohammed, & Komatil, 2015;Vainikainen, Hautamaki, Hotulainen, & Kupiainen, 2015).…”
Section: Categories Of Generic Skillsmentioning
confidence: 99%
“…Previous studies conducted on PBL, in different countries and in various field, have shown its effectiveness in developing students' learning skills. These include acquisition of subject content/knowledge (Hande, Mohammed & Komattil, 2014), life-long learning (Hosseini & Assareh, 2011), critical thinking (Yuan et. al, 2008), problem solving skills (Bigelow, 2004) and language skills (Mardziah H. Abdullah & Tan, 2008;Norzaini Azman & Shin, 2012;Othman & Ismail Ahamad Shah, 2013).…”
mentioning
confidence: 99%